VALUABLE ATTITUDE TO THE MOTHERHOOD AMONG HIGH SCHOOL GIRLS: STATE AND METHODS OF ITS FORMATION - Shakhrai, Valentyna (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article raises the problem of the importance of formation of the valuable attitude to the motherhood among high school girls in the modern conditions of social development, primarily related to the spread of such a phenomenon as “deviant motherhood”, which significantly reduces implementation of maternal function among female youth. The purpose of the study is to clarify the state of formation of the valuable attitude towards motherhood among high school girls and to identify certain aspects of its formation in the modern socio-cultural conditions. The essence of the concepts “valuable attitude towards motherhood” and «formation of the valuable attitude towards motherhood among high school girls» are found out. The components of the valuable attitude towards motherhood and indicators of its manifestation are determined. The analysis of the conducted empirical research was carried out to determine the levels of formation of the valuable attitude towards motherhood among high school girls (based on the developed questionnaire, which contains 37 questions). The levels of formation of the value attitude towards motherhood among high school girls were established: appropriate (13.9 % of girls); infantile (58.3 % girls); indifferent (27.8 % of girls). It was concluded that the level of the formation of the valuable attitudes towards motherhood among high school girls is insufficient, which requires the development of forms and methods of formation of the valuable attitude towards motherhood among high school girls. It is emphasized that student club is an effective form of work with students of the high school age and it is suggested to use it in the upbringing program in the girls’ club. “Motherhood is happiness” that provides four areas of work (diagnostic, informational-educational, training, practical), which can be implemented with the help of these methods: mini-lectures, conversations, discussions, the case study method, training, discussion of literary works, learning games, songs, making toys etc. The scientific novelty of the study consists of clarification of the concepts of “valuable attitude towards motherhood” and “formation of the valuable attitude towards motherhood among high school girls”, determination of the state of formation of the valuable attitude towards motherhood among modern high school girls, development a club program for girls with the aim of forming the valuable attitude towards motherhood. The article will be useful for scholars and educators who are interested in the problems of modern education.